Lateks sebagai bahan tambah kepada konkrit asfalt - Riza Atiq O.K. Rahmat,; Amiruddin Ismail,; Yeong , Tuck Wai (1997)
Mixing a small quantity of latex into bitumen in the road surface construction was found to increase its age and strengths. It was found by mixing 6% latex into bitumen to be the optimum content to increase its age. However this mixture was too viscous and to the extent of reducing its workability. In this Study, the characteristics of concrete asphalt using 6% latex by weight of the bitumen were compared with the natural bitumen and with the bitumen mixture comprising of 3% latex. The 3% latex was chosen because Kuala Lumpur City Hall and Public Works Department have fixed a 3% latex content in asphalt concrete pavement. Marshall specimens were prepared for the three types of bitumen mixture and were tested and analysed. All these specimens passed the Marshall stability tests. The 3% bitumen latex mixture has increased the Marshall stability from 7.73 kN to 13.30 kN but has increased the optimum bitumen content from 5.05% to 5.14% when compared to the natural bitumen. Nonetheless, the 6% bitumen latex mixture has increased the Marshall stability to 12.17% and has reduced its bitumen optimum content to 4.95%